Effective Risk Assessment Models for Construction Industry - Topal, Sabriye (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The construction industry is known to have overwhelming numbers of occupational accidents worldwide, which attribute to continuous demand for care and improvement. Due to this enormous risk, identifying the contributing factors should be prioritized for accident prevention and hazard control. However, it is evident that the lack of enforcement and preventive inspection in Turkish Republic of North Cyprus causes the necessity of new approaches for improvement. To begin with, we collected data from the Ministry of Labor to gather information on accident modes, work trades, and loss of working days due to occupational accidents. Subsequently, checklists were prepared based on the rules and regulations in North Cyprus construction industry. There is no risk assessment model study in the literature related to North Cyprus construction industry. The main aim of the thesis is to develop an effective risk assessment models for North Cyprus construction industry to create a better working environment for employees by minimizing the risk at the site and taking the precautions. Various risk assessment models were identified to be modified, developed then applied in the North Cyprus construction industry: traditional, preliminary, fuzzy, and modified fuzzy risk assessment models. These models implemented in the North Cyprus construction industry to determine the most suitable and effective one. Apart from the insufficiency in general site safety, this study shows that the safety barriers are not adequate, accident frequency and severity of accidents are high; especially for falling from a height. Generally, worker characteristics were composed of disproportionally low experienced workers, and the training given was found to be inadequate. In addition, the risk level for each accident mode and the hazard index for different construction sites are calculated. All of these helped us develop a special Risk Assessment Model unique to North Cyprus circumstances

ÖZ: Dünya genelinde en çok sayıda iş kazasının inşaat sektöründe olduğu bilinmektedir. Bunun sebebi ise, inşaat sektörünün doğasında var olan tehlikenin sürekli bakım ve iyileştirme gerektiren bir alan haline gelmesinden kaynaklanmaktadır. Risk yüksektir ve odak, kazayı önleme ve tehlike kontrolü için iyi bir yapıyı sürdürmeyi zorlaştıran faktörlerin belirlenmesi üzerinde olmalıdır. Ayrıca, Kuzey Kıbrıs Türk Cumhuriyetin'de yaptırım ve önleyici denetim eksikliğinin, iyileştirme için yeni yaklaşımların gerekliliğine neden olduğu görülmektedir. Bu çalışmada, öncelikle Çalışma Bakanlığı'ndan veri topladık ve kaza şekilleri, iş tanımları ve iş günü kayıplarına göre verileri düzenledik. İkinci olarak, Kuzey Kıbrıs inşaat sektöründeki kural ve yönetmeliklere dayalı olarak bir kontrol listesi hazırlanmıştır. Kuzey Kıbrıs’ta risk degerlendirme modelleri ile ilgili bir çalışma bulunmamatadır. Bu çalışmanın esas amacı Kuzey Kıbrıs inşaat endüstrisinde kullanılmak üzere bir risk değerlendirme modeli geliştirmek ve böylelikle çalışanlar için riski en aza indirip daha iyi bir çalıştırma ortamı yaratmaktır. Bu sebeble, Kuzey Kıbrıs inşaat endüstrisinde farklı risk değerlendirme modelleri düzenlenip geliştirilmiş ve ardından uygulanmışıtr. Bunlar, geleneksel, ön, bulanık ve değiştirilmiş bulanık risk değerlendirme modelleri die adlandırılmaktadır. Farklı modellerin inşaat sahalarında uygulanma amacı en uygun ve etkili modeli seçebilmek içindir. Bu çalışma, genel saha güvenliğinin ve güvenlik bariyerlerinin yetersiz olduğunu, özellikle de yüksekten düşmelerin şiddetinin yüksek olduğunu ve sık sık kaza yapma olasılıkları bulunduğunu göstermektedir. Genel işçi özelliğine göre az sayıda deneyimli işçi olduğu ve işçilere verilen eğitim sayısının yeterli olmadığı belirlenmiştir. Her kaza tipi için risk seviyesi ve farklı inşaat durumları için tehlike indeksi hesaplanmıştır. Tüm bu çalışma, Kuzey Kıbrısta kullanılaibilecek örgün modeli geliştrimemize yardımcı olmaktadır.
Doctor of Philosophy in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2022. Supervisor: Asst. Prof. Dr. Emine Atasoylu.
Keywords: Industrial Engineering Department; Industrial safety--engineering; Preventing Accidents--Risks--Assessment--Safety measures; Industrial and Production Engineering--Risk Assessment--Construction Industry; Risk assessment models; hazard index; occupational accidents; accident prevent